2018
DOI: 10.1080/13607863.2017.1423025
|View full text |Cite
|
Sign up to set email alerts
|

Pain intensity, depressive symptoms, and functional limitations among older adults with serious mental illness

Abstract: These findings demonstrate that pain and depressive symptoms may be linked to functional limitations. Clinicians and researchers in the mental health field should better address pain-related activity interference among older adults with SMI, especially among those with higher pain intensity and elevated depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Another key finding with clinical applications was that caregivers who reported more PWD pain interference cared for PWDs for whom they perceived had greater depression than caregivers who reported less interference. Associations between caregiver perception of PWD depression and pain interference are consistent with literature on the positive association between depression and symptom reports among PWDs (Wang et al, 2018), older adults in general (Molton & Terrill, 2014), and other vulnerable groups of older adults (e.g., those with serious mental illness (Brooks et al, 2019)). Pain interference may limit activity and lead PWDs to withdraw from social, physical, recreational, and otherwise enjoyable or meaningful activities.…”
Section: Discussionsupporting
confidence: 85%
“…Another key finding with clinical applications was that caregivers who reported more PWD pain interference cared for PWDs for whom they perceived had greater depression than caregivers who reported less interference. Associations between caregiver perception of PWD depression and pain interference are consistent with literature on the positive association between depression and symptom reports among PWDs (Wang et al, 2018), older adults in general (Molton & Terrill, 2014), and other vulnerable groups of older adults (e.g., those with serious mental illness (Brooks et al, 2019)). Pain interference may limit activity and lead PWDs to withdraw from social, physical, recreational, and otherwise enjoyable or meaningful activities.…”
Section: Discussionsupporting
confidence: 85%
“…However, this difference could be due to pain or other comorbidities. In 2018 Brooks et al demonstrate that pain and depressive symptoms may be linked to functional limitations [71], also Freynhagen et al confirmed that depression and anxiety appear to be more common in patients with neuropathic pain compared to those without [72]. Based on the second wave of Healthcare for Communities (HCC2), Brennan Braden et al discovered that chronic pain leads to more use of mental wellbeing services and higher distress in healthcare settings among older adults [73].…”
Section: Discussionmentioning
confidence: 99%
“…Pain intensity was assessed using the self-report, single pain chart item from the Dartmouth-Northern New England Primary Care Cooperative Information Project (COOP) Functional Assessment Charts (Nelson et al 1987). Although pain intensity is based on a self-report and single-item Likert-type scale, it is the standard pain measurement used in clinics and community-based health services (Brooks et al 2018a). Respondents rate their pain during the past 2 weeks on a 5-point Likert-type scale ranging from 1 (no pain) to 5 (severe pain) according to illustrations depicting corresponding pain levels.…”
Section: Predictor Variablementioning
confidence: 99%
“…Moderate-to-severe levels of intense pain significantly affects 35% of adults with schizophrenia (Stubbs et al 2014), which is consistent with rates in the general population (Murray et al 2013). Remarkably though, little is known about intense pain and its impact in schizophrenia research (Brooks et al 2018a). Given that late-life pain interferes with agingrelated adjustment and is associated with depressive symptoms in U.S. older adults without serious mental illnesses (Reid et al 2015), describing the physical and mental health characteristics of pain is critical among high-risk older adults experiencing serious mental illnesses (Almeida et al 2014;Bartels 2004).…”
Section: Introductionmentioning
confidence: 99%